STRATEGI PENGEMBANGAN USAHA KECIL KERIPIK TEMPE DI DESA BULUH RAMPAI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Sulistiani, Novi; Sumarno, Sumarno; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : One type of small business in Indragiri Hulu is tempeh chips. Analysis of the strategies needed to develop small businesses tempeh chips in the village Buluh Rampai Seberida District of Indragiri Hulu in fact small businesses tempeh chips is one of the livelihoods of people in rural Buluh Rampai and should this business is more advanced because it has the advantages of the product . In addition it should be reviewed appropriate development strategy to boost small businesses tempeh chips were analyzed using SWOT matrix . The purpose of this study was to determine alternative effective strategy implemented to develop small businesses tempeh chips. Research was conducted on employers tempeh crisps , as many as eight business units. The results showed that small businesses tempeh chips in the village Buluh Rampai Seberida District of Indragiri Hulu in position V with a concentration strategy through horizontal integration or stability ( no change in revenue ) . alternative strategies that can be applied to develop small businesses tempeh chips in the village Buluh RampaiDistrict of Seberida Indragiri Hulu namely Maintaining tempeh chips as typical food from the public , the use of labor from the surrounding area to increase production , optimize the management of the business to raise capital so that goods produced more maximum , more reintroduce that tempe chips as snack center in Desa Buluh Rampai Seberida District of Indragiri Hulu. Keywords : Strategy Development , Small Business